2017
DOI: 10.1002/cncr.30693
|View full text |Cite
|
Sign up to set email alerts
|

7‐year follow‐up after stereotactic ablative radiotherapy for patients with stage I non–small cell lung cancer: Results of a phase 2 clinical trial

Abstract: Background We evaluated the efficacy, pattern of failure, and toxicity of stereotactic ablative radiotherapy (SABR) for medically inoperable clinical stage I non-small cell lung cancer (NSCLC) in a prospective clinical trial with 7 years follow-up. Methods Eligible patients with histologically confirmed NSCLC and PET clinically staged I disease were treated with SABR (50 Gy in 4 fractions). The primary endpoint was progression-free survival (PFS). Patients were followed with CT/PET-CT every 3 months for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
108
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(126 citation statements)
references
References 32 publications
6
108
1
4
Order By: Relevance
“…It has been shown that using RT to control primary and metastatic tumors can reduce intra‐thoracic disease burden, bronchial/vascular compression, and pulmonary symptoms . In addition, local control of primary and metastatic tumors might result in better OS . Recently, a phase III randomized controlled trial (RCT) showed that thoracic radiotherapy (TRT) also improved OS of patients with extensive‐stage small cell lung cancer (SCLC) who responded to chemotherapy .…”
Section: Objectivesmentioning
confidence: 99%
“…It has been shown that using RT to control primary and metastatic tumors can reduce intra‐thoracic disease burden, bronchial/vascular compression, and pulmonary symptoms . In addition, local control of primary and metastatic tumors might result in better OS . Recently, a phase III randomized controlled trial (RCT) showed that thoracic radiotherapy (TRT) also improved OS of patients with extensive‐stage small cell lung cancer (SCLC) who responded to chemotherapy .…”
Section: Objectivesmentioning
confidence: 99%
“…RTOG 0236 suggested that peripheral stage I non‐small cell tumors treated with SABR could achieve acceptable local control (LC) and overall survival (OS) . A phase 3 randomized trial comparing SABR with surgery has suggested that SABR was better tolerated and might lead to better OS compared with surgery for operable clinical stage I NSCLC . In the past, we preferred to treat peripheral lung tumors with SABR, which has been proven safe and efficient.…”
Section: Introductionmentioning
confidence: 99%
“…Lobectomy is undoubtedly the standard of care for operable early‐stage NSCLC in the current situation where there are no randomized trials comparing SABR with lobectomy. However, most of the previously reported studies on lobectomy included young patients with an average age of 65 years, while those on SABR included older patients with an average age of 75 years . As a result, it is difficult to compare the overall survival between the two procedures directly using the existing research designs including patients of different age distributions.…”
Section: Discussionmentioning
confidence: 99%
“…Solitary distant metastasis or secondary primary lung cancer also could be re‐treated with SABR or surgery. However, our tumor board determined that the likelihood of either of these procedures affecting the outcome would be low because the probability of occurrence is unknown, could fall within a very wide range and be similar in both groups . As a result, all distant metastases were not considered as candidates for salvage treatment and secondary primary lung cancer was not reflected in this scenario to simplify the Markov model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation